Sacrificing leisure for clean energy fuel: A decomposition analysis of time poverty - Martey, Edward; Etwire, Prince M.; Mockshell, Jonathan; Asante‐Addo, Collins (Wiley, 2025)
Given the extended hours demanded by the labour market and the health risks posed by pollution from nonrenewable energy sources, the question of whether households are willing to prioritise clean energy over leisure remains unresolved. This study addresses this gap by investigating the impact of time constraints, encompassing both paid and unpaid work, on the Multidimensional Energy Poverty Index (MEPI) using data from the seventh round of the Ghana Living Standards Survey (GLSS 7). Our findings indicate that households experiencing time constraints are more inclined to adopt clean energy fuels. A decomposition analysis of time constraints reveals that while those stemming from paid work encourage the adoption of clean energy fuels, those associated with unpaid work hinder it. This suggests that households prioritise clean energy when faced with time pressures related to paid employment. Our results hold across various estimation methods and withstand robustness checks using different time and energy poverty metrics. The adverse impact of time constraints on energy poverty is particularly pronounced in rural areas, male‐headed households and communities with accessible roads. We posit that household income serves as a key mechanism through which time constraints influence energy poverty.